SYNTHESIS OF EDEINE DERIVATIVES AS AN APPROACH TO TACKLE THE ANTIBIOTIC CRISIS - Johnson, Emma (My University, 2019)
Abstract The current rise in antibiotic resistance and lack of discovery of new antibiotics in recent years has caused an antibiotic crisis. A strategy for overcoming this crisis is to relook at previously discarded antibiotics and with medicinal chemistry, use their structure as a scaffold for the development of a new antibiotic. Edeines are a group of antimicrobials discovered by Kurylo-Borowska in 1959 that were discarded for toxicity and this work aimed to use edeine for the structural basis in the development of a novel antibiotic. Using both solution phase and solid phase peptide synthesis ꞵ-tyrosine-L-isoseryl-diaminopropionic acid was synthesized to develop a synthetic strategy for the peptide synthesis of Edeine A. Solid phase peptide synthesis techniques were used to synthesize two simplified edeine analogues which demonstrated that the amino acid 2,6-diamino-7-hydroxylazaleic acid was necessary for antimicrobial activity. A synthetic strategy for the synthesis of 2,6-diamino-7-hydroxylazaleic acid (DAHAA) using ring closing metathesis and aminohydroxylation was developed and starting materials were synthesized. Using solid phase synthesis and the strategy for synthesizing DAHAA, a library of edeine analogues could be made using parallel synthesis and assayed for specific antimicrobial activity. This could lead to the development of a lead antibiotic which used edeine as a structural scaffold, therefore a novel antibiotic could be clinically used without large scale resistance present in the environment like the currently used antibiotics.
Keywords: edeine; organic chemistry; synthesis; antibiotic